Clinical standards for drug-susceptible pulmonary TB - Akkerman, O. W.; Duarte, R.; Tiberi, S.; Schaaf, H.S.; Lange, C.; Alffenaar, J.W.C.; Denholm, J.; Carvalho, A.C.C.; Bolhuis, M.S.; Borisov, S.; Bruchfeld, J.; Cabibbe, A.M.; et al. (International Union Against Tuberculosis and Lung Disease (The Union), 2022)
BACKGROUND: The aim of these clinical standards is to provide guidance on 'best practice' for diagnosis, treatment and management of drug-susceptible pulmonary TB (PTB). METHODS : A panel of 54 global experts in the field of TB care, public health, microbiology, and pharmacology were identified; 46 participated in a Delphi process. A 5- point Likert scale was used to score draft standards. The final document represents the broad consensus and was approved by all 46 participants. RESULTS : Seven clinical standards were defined: Standard 1, all patients (adult or child) who have symptoms and signs compatible with PTB should undergo investigations to reach a diagnosis; Standard 2, adequate bacteriological tests should be conducted to exclude drug-resistant TB; Standard 3, an appropriate regimen recommended by WHO and national guidelines for the treatment of PTB should be identified; Standard 4, health education and counselling should be provided for each patient starting treatment; Standard 5, treatment monitoring should be conducted to assess adherence, follow patient progress, identify and manage adverse events, and detect development of resistance; Standard 6, a recommended series of patient examinations should be performed at the end of treatment; Standard 7, necessary public health actions should be conducted for each patient. We also identified priorities for future research into PTB. CONCLUSION: These consensus-based clinical standards will help to improve patient care by guiding clinicians and programme managers in planning and implementation of locally appropriate measures for optimal person-centred treatment for PTB.